Whiteness, Afrikaans Language Politics and Higher Education Transformation at Stellenbosch University - Kees (C. S.) van der Waal; Monica du Toit (Transforming Transformation in Research and Teaching at South African Universities, 2018)
The effect of prioritising Afrikaans in tertiary education over access for black students needing to study in English was core to the struggle for transformation at Stellenbosch University (SU) between 2002 and 2017. Attempts of successive managements to open the university to black students by increasing tuition in English led to a spiralling taaldebat (language debate) expressing the anxiety and anger of white Afrikaans-speakers. In 2016 the black-led student movement Open Stellenbosch forced a breakthrough, moving the focus on the right to language identity to the right to access. In the period framed by the shift from identity to access,